2020
DOI: 10.3390/molecules25214911
|View full text |Cite
|
Sign up to set email alerts
|

Application of NF Polymeric Membranes for Removal of Multicomponent Heat-Stable Salts (HSS) Ions from Methyl Diethanolamine (MDEA) Solutions

Abstract: This study presents an efficient and scalable process for removing the heat-stable salts (HSS) ions from amine solution while recovering methyl diethanolamine (MDEA) solution for its reuse in gas sweetening plants. The presence of HSS in the amine solution causes the loss of solvent capacity, foaming, fouling, and corrosion in gas sweetening units so their removal is crucial for a more well-performing process. Furthermore, the recovery of the amine solution can make the sweetening step a more sustainable proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 58 publications
(71 reference statements)
0
10
0
Order By: Relevance
“…NF experiments were performed at the laboratory-scale using a cell equipped with an NF-3 polyamide flat-sheet membrane (Sepro Membranes, Inc., Oceanside, CA, USA) operated in cross-flow ( Figure 1 ) (as were conducted in the preveous study [ 46 ]). The effective area was 0.0113 mThe specifications provided by the manufacturer indicated that the NF-3 polymeric membrane consists of three layers, including the polyamide surface layer, and polyester support with a polysulfone substrate.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…NF experiments were performed at the laboratory-scale using a cell equipped with an NF-3 polyamide flat-sheet membrane (Sepro Membranes, Inc., Oceanside, CA, USA) operated in cross-flow ( Figure 1 ) (as were conducted in the preveous study [ 46 ]). The effective area was 0.0113 mThe specifications provided by the manufacturer indicated that the NF-3 polymeric membrane consists of three layers, including the polyamide surface layer, and polyester support with a polysulfone substrate.…”
Section: Methodsmentioning
confidence: 99%
“…In a study, we investigated the separation of a multicomponent mixture of HSS ions from the different concentrations of MDEA solution via NF membrane. The result showed that the separation efficiency of ions was close to 80% [ 46 ]. Also, in another work, we estimated transport parameters for a binary system of ions in amine solution through NF membrane [ 47 ].…”
Section: Introductionmentioning
confidence: 99%
“…An 80% retention of TSSs in the process of nanofiltration of a multicomponent mixture of ionic impurities in an MDEA solution was shown [105]. In their next study, the authors presented a model for the transport of TSS ions from MDEA solutions during nanofiltration for different flow rates of the initial absorbent, transmembrane pressure, and compositions of the initial absorbent [106].…”
Section: Membrane Technologies To Improve Efficiency Of Amine Co 2 Purificationmentioning
confidence: 97%
“…There have been a number of review studies focused on the existing HSS removal methods [12][13][14]. The common method for solvent reclaiming from HSS is distillation [8,17], though alternative techniques exist and include-removal of HSS anions using ion-exchange resins [18,19], capacitive deionization [20,21], concentration of HSS using nanofiltration [22,23], and electromembrane treatment methods [24][25][26]. Direct and bipolar electrodialysis are applicable for treating MEA-based post-combustion CO 2 capture solvents [27][28][29][30][31][32] and diethylamine recovery with simultaneous acid production [33,34].…”
Section: Introductionmentioning
confidence: 99%